Amendment of section 8(d)(iv) of the South African Competition Act 89 of 1998 as a key tool to adjudicate exclusionary abuse - Van Heerden, C.M. (Corlia) (University of Pretoria, 2019)
Mini Dissertation (LLM)--University of Pretoria, 2018.